Investigation of denugue virus envelope gene quasispecies variation in patient samples : implications for virus virulence and disease pathognesis - Love, Hannah (Cranfield University, 2011)
Due to the error-prone nature of RNA virus replication, each dengue virus (DV) exists as a quasispecies within the host. To investigate the hypothesis that DV quasispecies populations affect disease severity, serum samples were obtained from dengue patients hospitalised in Ragama, Sri Lanka. From the patient sera, DV envelope glycoprotein (E) genes were amplified by high-fidelity RT-PCR, cloned, and multiple clones per sample sequenced to identify mutations within the quasispecies population. A mean quasispecies diversity of 0.018% was observed, consistent with reported error rates for viral RNA polymerases (0.01%; Smith et al., 1997). However, previous studies reported 8.9 to 21.1-fold greater mean diversities (0.16% to 0.38%; Craig et al., 2003; Lin et al., 2004; Wang et al., 2002a). This discrepancy was shown to result from the lower fidelity of the RT-PCR enzymes used by these groups for viral RNA amplification. Previous studies should therefore be re-examined to account for the high number of mutations introduced by the amplification process. Nonsynonymous mutation locations were modelled to the crystal structure of DV E, identifying those with the potential to affect virulence due to their proximity to important structural features. No correlation was observed between the extent of quasispecies variation and disease severity. However, genome-defective quasispecies variants, and variants with surface accessible amino acid substitutions, or those proximal to the fusion peptide, proposed receptor binding sites, or other E oligomers, were observed predominantly in patients with severe dengue. Recombinant virus-like particles were produced for nine quasispecies variants, and the effects of the mutations on protein function assessed. Altered heparin binding abilities were demonstrated for four of the nine variants, indicative of differing cell attachment capabilities. Further work is required to assess differences in antibody binding, replication efficiency, virion and oligomer assembly, low pH-induced conformational changes required for fusion, and transmissibility of variants.